Edukasi Pemanfaatan Kulit Petai sebagai Biopestisida untuk Pengendalian OPT di Desa Sungai Rotan, OI - Ika Paridawati; Delfy Lensari; Sri Amelia Junianti; Raja Faqih Abdillah (Universitas Muhammadiyah Palembang, 2026)
Utilizing organic household waste can be an environmentally friendly alternative for controlling plant pests (OPT). This educational activity aims to increase public knowledge regarding the use of petai peel waste (Parkia speciosa) as a biopesticide ingredient and how to apply it to cultivated plants for sustainable agriculture in Sungai Rotan Village, Ogan Ilir Regency. The activity method is carried out through counseling, discussion and demonstration of making biopesticide from petai peel. The results of the activity showed an increase in public understanding about household waste management and its use as a natural pesticide with an increase in the pre-test score is 40 to post-test score is 80. This activity was attended by 50 participants consisting of farming communities in Sungai Rotan Village and KKN students. It is hoped that the use of petai peel as a biopesticide can support more environmentally friendly agricultural practices and reduce dependence on chemical pesticides.